PUSAT BUDAYA MELAYU KALIMANTAN BARAT - Waldi Apriadi; Uray Fery Andi; Zairin Zain (JMARS: Jurnal Mosaik Arsitektur, 2021)
There have been many attempts by cultural actors to promote and preserve Malay Culture in West Kalimantan, but they still face obstacles that make everything hampered. As the interest of the next generation to study and preserve Malay Culture is decreasing, cultural promotion activities are modest, marketing of typical handicrafts that are difficult to market, and the Malay Culture community does not yet have a suitable place to work. Anticipating this, a forum is needed to preserve, demonstrate, maintain and develop West Kalimantan Malay Culture. The final project of the Malay Cultural Center aims to create a center for the preservation of Malay Culture in West Kalimantan. The design method of the West Kalimantan Malay Cultural Center was carried out in several stages, namely ideas, theoretical review, data collection, analysis, synthesis, pre-design, and design. The design concept of the Malay Cultural Center is based on the design elements of the Malay settlement area. The design analysis resulted in several building functions but broadly divided into three functions, namely primary function (performance building), secondary function (training building, art gallery building), and management function (management building, souvenir kiosk). Analysis of the formation of the pattern of the area is taken from the elements of the formation of the Malay area in general and is combined with the shape of the design location. The characteristics of the building follow the form of a West Kalimantan Malay settlement in the form of a typical building on stilts and a pyramid roof / saddle with space tailored to the needs of the user.